Peran Remaja Dalam Memaksimalkan Fungsi Mushola Pada Masa Pandemi - Mas'ut, Mas'ut; Lutfiana Rahmawati, Fina; Fuad U., Muhamad (Universitas Pangeran Diponegoro Nganjuk, 2022)
Moderation of religion is a middle way of religion in accordance with the meaning of moderation earlier. With religious moderation. A person is not extreme and does not exaggerate when carrying out his religious teachings. People who practice it are called moderates. However, at this time we are experiencing pandemic constraints which have disrupted all activities in society because of the protocols that must be followed. This assistance aims to make the mosque in Prayungan Village, Lengkong District, Nganjuk Regency more prosperous. Making the prayer room not only a routine place for carrying out mahdoh worship, but also a center for social activities. In the end we tried to embrace village youth to provide an understanding of the functions and roles of a musola, and in the end there were positive activities from the community service activities that we carried out, then many people were happy about these activities.